Linear polarization of x-ray photons in hyperfine-quenched transitions of polarized He-like ions - Bondarevskaya, Anastasia A.; Labzowsky, L.; Prozorov, A.; Plunien, G.; Liesen, Heinz-Dieter; Bosch, F. (Journal of physics. B, Atomic, molecular and optical physics, 2010)
The most important motivation for polarized heavy ion beams is the possibility of observing parity nonconservation effects in the hyperfine-quenched (HFQ) transitions in polarized He-like highly charged ions. In such ions these effects can reach unprecedented large values for atomic physics. Measurements require online diagnostics of the degree of the polarization of the ion beam. It is argued that this can be accomplished by the measurement of the Stokes parameters of the photons which are emitted with the process of HFQ transitions.
Gesehen am 08.02.2023